Presenting a Model to Understanding the Mentality of Audiences - Eskandari, Hamid; Hosseini Dana, Hamidreza (Journal of History Culture and Art Research, 2018)
As one of the key elements of mass communication process, the audience has always been of interest to mass media researchers and practitioners. The audience is important considering the realization of the economic goals of the media and the originality of the media content. This study used the ideas of previous studies in the field of communication and cultural studies, presented a model for understanding the public perception (PP), and modified the production of television programs using Delphi method according to the opinion of the experts that was finally approved by them. Experts' views and opinions were obtained with the questionnaire tool, the model was presented and with a total 78% of the opinions was confirmed in three parts of the accuracy of the components, relationship, and the explicitly of the model in describing the process. Thus, considering the fluidity and history of PP, it is suggested that PP should be constantly monitored and examined according to three factors - mass media contents, opinions of the experts, and published contents of social networks.